FUZZY-BASED ENGLISH WRITING WITH KEY-BASED ASSESSMENT - Hill, Janice (Physical and Mathematical Education, 2024)
Traditional assessment methods in education often rely on rigid grading structures that may fail to capture the nuances of language skills, especially in subjective areas like writing. This article explores how fuzzy logic, a mathematical system that handles imprecision, can enhance English writing assessment by providing a more flexible, holistic view of students' abilities.Formulation of the problem. English writing is a fairly subjective practice that, due to its interpretative nature, can often present instructors with a challenge when it comes to administering evaluations that are impartial and purely objective. This paper aims to propose a proper way of investing rigor and focus on the core principles of English writing into the process of reviewing student work through the applied integration of mathematics’ fuzzy logic.Materials and methods. The resources included in this article are a variety of robust and innovative works of academic literature that have proven their relevance and advancement to the field of mathematics and also pedagogical assessment methodology. The primary studies and their respective demonstrations of research are productively referenced throughout this paper to concretely elucidate how fuzzy logic can make a difference in forming adequate feedback for English writing students.Results. The results point to fuzzy logic-based assessments of English writing having merit that is long overdue in English classrooms.Conclusions. Overall, this article recognizes that fuzzy logic-based assessments of English writing are a ruthlessly efficient, convenient, and innovative strategic approach to scrutinizing student work with fairness, absence of creative bias, and extensiveness.
Keywords: Fuzzy Logic; Writing Assessment; Writing Composition; COG Technique; Defuzzification